Optimasi Biaya Pemupukan Tanaman Padi pada Kelompok Tani Rambahan Sakato, Desa Nyiur Melambai Pelangai menggunakan Metode Kuhn Tucker - Safitri, Elfira; Basriati, Sri; Soleh, Mohammad; Yulanda, Rahmi (KUBIK: Jurnal Publikasi Ilmiah Matematika, 2023)
The Rambahan Sakato Farmer Group, Nyiur Melambai Pelangai Village, West Sumatra is a farmer groups that produces various types of food, one of which is rice plants. One of the factors that support plants to grow optimally is the availabity of nutrients in sufficient quantities in the soil. There are four types of fertilizers used in the fertilization of rice plants, namely SP-36 fertilizer, Urea fertilizer, Phonska fertilizer and KCL fertilizer. This study aims to optimal solution in determining in amount of fertilizer in rice plants with the minimum cost using the Kuhn Tucker Method. The method used in this research is the Kuhn Tucker method. The solution to the Kuhn-Tucker method is the same as the Lagrange method, namely calculating the value (x, Î», S) and calculating the value of f (x). The process of finding values (x, Î», S) uses matrix multiplication. Based on the research results, it was found that the Rambahan Sakato farmer group needed to provide 1 sack of SP-36 fertilizer, 3 sacks of urea fertilizer, 16 sacks of Phonska fertilizer and did not need to provide KCL fertilizer at a minimum cost of Rp. 2,710,000.